Dampak Pupuk Organik Padat Dan Pupuk Organik Cair Daun Gamal (Gliricidia sepium) Untuk Pertumbuhan Dan Produksi Tanaman Cabai Rawit (Capsicum frutescens L.): The Impact of Solid Organic Fertilizer and Liquid Organic Fertilizer from Gamal Leaves (Gliricidia sepium) for the Growth and Production of Cayenne Pepper Plants (Capsicum frutescens L.) - Puteri Aprilani; Mita Purnama; Mahdalena (Agrifarm : Jurnal Ilmu Pertanian, 2023)
The research method used was a Randomized Block Design with a 2x4 Factorial Experiment consisting of 3 replications. The first factor is solid organic fertilizer (P) which consists of 2 types, namely: Solid decanter fertilizer (Ps): 5 Kg/Polybag; Manure (Pk): 5 Kg/Polybag. The second factor is gamal leaf liquid organic fertilizer (G) which consists of 4 levels, namely: G0: (control); G1: 10% concentration; G2: 30% concentration and G3: 50% concentration.           The results of the research showed that the treatment of giving gamal leaf liquid organic fertilizer with the lowest concentration, namely G1 (10%), had a significant effect on the fresh fruit weight parameters per plant with the best average weight of fresh fruit per plant being 137.00 g. Providing solid organic fertilizer of the decanter type did not have a significant effect on all parameters. Providing solid organic fertilizer of the chicken manure type had a significant effect on the average height growth of plants at 30 DAP, 60 DAP, 75 DAP, 90 DAP, stem diameter at 15 DAP, 45 DAP, 60 DAP, 90 DAP, and fresh fruit weight per plant.           The interaction of solid organic fertilizer and liquid organic fertilizer with gamal leaves had a significant effect on plant height at 15 DAP, stem diameter at 90 DAP, and fresh fruit weight per plant but had no significant effect on other parameters. The best treatment interaction was PkG1 with a fresh fruit weight of 221.00 gr. Keywords : Solid, Liquid, Fertilizer, Gamal Leaves